Multilayered Security and Privacy Protection in Car-to-X Networks Solutions from Application down to Physical Layer - Stübing, Hagen; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2013)
Car-to-X (C2X) communication in terms of Car-to-Car (C2C) and Car-to-Infrastructure (C2I) communication aims at increasing road safety and traffic efficiency by exchanging foresighted traffic information. Thereby, security and privacy are regarded as an absolute prerequisite for successfully establishing the C2X technology on the market. Towards the paramount objective of covering the entire ITS reference model with security and privacy measures, Hagen Stübing develops dedicated solutions for each layer, respectively. On application layer a security architecture in terms of a Public Key Infrastructure is presented, which provides low complexity and operational costs, while at the same time security and privacy constraints are preserved. On facility layer complementary security solutions based on mobility data verification are proposed, which promise efficient message content protection at a low computational complexity. On network layer a privacy protocol is presented aiming at a creation of cryptographic mix zones by means of group keys, which enhance privacy towards a global adversary. On physical layer a technique denoted as Secure C2X Beamforming is presented, which enhances privacy and security by means of radiation pattern control.   Contents ·         Security and Privacy in Car-to-X Communication Networks ·         Public Key Infrastructure ·         Mobility Data Verification ·         Privacy Protocols ·         Secure Car-to-X Beamforming   Target groups ·         Researchers and students in the field of security and privacy in mobile and vehicular ad hoc networks. ·         Practitioners in the field of security and privacy protocol design in vehicular communication networks.   The author Hagen Stübing completed his doctoral thesis at the department of Integrated Circuits and Systems Lab, Technische Universität Darmstadt, under the supervision of Prof. Dr.-Ing. Sorin A. Huss.
Security and Privacy in Car-to-X Communication Networks -- Public Key Infrastructure -- Mobility Data Verification -- Privacy Protocols -- Secure Car-to-X Beamforming.
Keywords: Input-output equipment (Computers).; Computer organization; Input/Output and Data Communications; Computer Systems Organization and Communication Networks